2015
DOI: 10.1116/1.4914949
|View full text |Cite
|
Sign up to set email alerts
|

Improved surge protection of flip-chip gallium nitride-based HEMTs by metal-semiconductor-metal two-dimensional electron gas varactor

Abstract: In this paper, the authors report on the development of aluminum gallium nitride/gallium nitride (AlGaN/GaN) high electron mobility transistors (HEMTs) with improved surge protection characteristics provided by a metal-semiconductor-metal two-dimensional electron gas (MSM-2DEG) varactor connected in series to the gate of each HEMT. Under an electrostatic discharge surge stress of 1100 V or less, HEMTs that incorporate this protection feature do not exhibit any changes because the surge stress is directly block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This component has been widely studied and reported [9][10][11][12][13][14][15]. We have proposed GaN-based 2DEG MSM varactors as the anti-surge components connected in series between the antenna and the backend circuits, as shown in Figure 1 [16], and we have demonstrated that this design protects the back-end HEMT element from electrostatic discharge (ESD) [17]. In this study, we further apply this protection concept to MEMP attacks.…”
Section: Introductionmentioning
confidence: 97%
“…This component has been widely studied and reported [9][10][11][12][13][14][15]. We have proposed GaN-based 2DEG MSM varactors as the anti-surge components connected in series between the antenna and the backend circuits, as shown in Figure 1 [16], and we have demonstrated that this design protects the back-end HEMT element from electrostatic discharge (ESD) [17]. In this study, we further apply this protection concept to MEMP attacks.…”
Section: Introductionmentioning
confidence: 97%